Haploinsufficiency of ABL1 is associated with dominant isolated omphalocele - Caroline M. Kolvenbach; Caroline M. Kolvenbach; Caroline M. Kolvenbach; Öznur Yilmaz; Filipa M. Lopes; Jeshurun C. Kalanithy; Jeshurun C. Kalanithy; Katharina Lemberg; Katharina Lemberg; Vineeta Sharma; Amar J. Majmundar; Matthias Geyer; et al. (Frontiers in Cell and Developmental Biology)
Omphalocele is a rare birth defect of the abdominal wall that results in herniation of the visceral organs through the umbilicus. To date, there are no identified genetic causes for non-syndromic isolated omphalocele. Exome sequencing in a four-generation multiplex family with isolated dominant omphalocele revealed a novel extended splice site variant (c.310 + 3A>C; p.?) in ABL1 that encoded a non-receptor tyrosine kinase. Consistent with in silico predictions, in peripheral blood, this variant leads to an alternatively spliced mRNA harboring a premature termination codon. Quantification of the ABL1 mRNA abundance showed its significant reduction in an affected allele carrier compared to a healthy control. These data indicate degradation of the aberrantly spliced transcript by non-sense-mediated decay (NMD), consistent with haploinsufficiency as the disease mechanism. Accordingly, exposure to different tyrosine kinase inhibitors during pregnancy is associated with a significantly higher risk of omphalocele in the exposed offspring. ABL1 is a causative gene for congenital heart defect and skeletal malformation syndrome (CHDSKM) and human ABL1 deficiency syndrome (HADS); CHDSKM is associated with gain-of-function while HADS is associated with 3′ truncating variants, likely escaping NMD. Therefore, allele-dependent mechanisms may explain the phenotypic diversity. In human embryos (45–47 days post fertilization), ABL1 was immunodetected in fibroblast-like cells in the umbilical cord as well as abdominal wall surface ectoderm, both of which are important sites for abdominal wall closure. In mouse embryos (embryonic days 14.5–15.5), wholemount in situ hybridization confirmed Abl1 expression in the umbilical cord. Our genetic and experimental findings provide evidence that ABL1 haploinsufficiency is the first monogenic cause for isolated dominant omphalocele.